Integral chain management of wildlife diseases. Issue 2 (4th February 2020) - Martel, An; Vila‐Escale, Mireia; Fernández‐Giberteau, Daniel; Martinez‐Silvestre, Albert; Canessa, Stefano; Van Praet, Sarah; Pannon, Pep; Chiers, Koen; Ferran, Albert; Kelly, Moira; Picart, Mariona; Piulats, Dolors; et al.
Abstract: The chytrid fungus Batrachochytrium dendrobatidis has caused the most prominent loss of vertebrate diversity ever recorded, which peaked in the 1980s. Recent incursion by its sister species B. salamandrivorans in Europe raised the alarm for a new wave of declines and extinctions in western Palearctic urodeles. The European Commission has responded by restricting amphibian trade. However, private amphibian collections, the main end consumers, were exempted from the European legislation. Here, we report how invasion by a released, exotic newt coincided with B. salamandrivorans invasion at over 1000 km from the nearest natural outbreak site, causing mass mortality in indigenous marbled newts ( Triturus marmoratus ), and posing an acute threat to the survival of nearby populations of the most critically endangered European newt species (Montseny brook newt, Calotriton arnoldi ). Disease management was initiated shortly after detection in a close collaboration between policy and science and included drastic on site measures and intensive disease surveillance. Despite these efforts, the disease is considered temporarily contained but not eradicated and continued efforts will be necessary to minimize the probability of further pathogen dispersal. This precedent demonstrates the importance of tackling wildlife diseases at an early stage using an integrated approach, involving all stakeholders and closing loopholes in existing regulations.